2015
DOI: 10.1007/s12035-014-9055-4
|View full text |Cite
|
Sign up to set email alerts
|

ASIC3 Is Required for Development of Fatigue-Induced Hyperalgesia

Abstract: An acute bout of exercise can exacerbate pain, hindering participation in regular exercise and daily activities. The mechanisms underlying pain in response to acute exercise are poorly understood. We hypothesized that proton accumulation during muscle fatigue activates ASIC3 on muscle nociceptors to produce hyperalgesia. We investigated the role of ASIC3 using genetic and pharmacological approaches in a model of fatigue-enhanced hyperalgesia. This model uses two injections of pH 5.0 saline into muscle in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 84 publications
6
60
0
1
Order By: Relevance
“…Quantitation of F4/80-stained muscle macrophages showed that the average number of macrophages was approximately 20.83 +/− 2.80 in 5 sections in gastrocnemius muscles treated with Clod and was significantly less than the number from PBS-Lipo which averaged 82.33 +/− 9.79 (P<0.0001), similar to prior data by us [17]. Twenty-four hours after the second injection of acidic saline, responses to repeated mechanical stimulation of the paw increased and muscle withdrawal thresholds significantly decreased bilaterally in control animals treated with PBS-Lipo (p<0.0001).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Quantitation of F4/80-stained muscle macrophages showed that the average number of macrophages was approximately 20.83 +/− 2.80 in 5 sections in gastrocnemius muscles treated with Clod and was significantly less than the number from PBS-Lipo which averaged 82.33 +/− 9.79 (P<0.0001), similar to prior data by us [17]. Twenty-four hours after the second injection of acidic saline, responses to repeated mechanical stimulation of the paw increased and muscle withdrawal thresholds significantly decreased bilaterally in control animals treated with PBS-Lipo (p<0.0001).…”
Section: Resultssupporting
confidence: 89%
“…Similarly, in human subjects infusion of acidic solutions into muscle produces pain and hyperalgesia both locally at the site of infusion but also in a referred pain site [15]. It is well known that ASICs are sensitive to H + and involved in acute and chronic muscle hyperalgesia [1;17;52;61]. In general, they are widely expressed nervous systems, including sensory nerves that innervate the skeletal muscle (muscle afferents)[1;35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined above, two injections of acidic saline into a single gastrocnemius muscle produce hyperalgesia not only at the site of injection but also in the contralateral muscle and viscera. Pharmacological blockade of ASIC3, with APETx2, at the first or second injection, prevents the development of the widespread long-lasting hyperalgesia (Karczewski et al, 2010, Chen and Chen, 2014, Gregory et al, 2015b), suggesting activation of ASIC3 on nociceptors innervating muscle is important for development of widespread hyperalgesia (Figure 3). Similarly, the hyperalgesia in the repeated acid model, or the fatigue-induced model, requires activation of acid sensing ion channel 3 (ASIC3) since the hyperalgesia does not in ASIC3 knockout mice (Sluka et al, 2003, Gregory et al, 2015a)(Figure 3).…”
Section: Alterations In Nociceptors May Underlie Some Of the Pathologmentioning
confidence: 99%
“…Pharmacological blockade of ASIC3, with APETx2, at the first or second injection, prevents the development of the widespread long-lasting hyperalgesia (Karczewski et al, 2010, Chen and Chen, 2014, Gregory et al, 2015b), suggesting activation of ASIC3 on nociceptors innervating muscle is important for development of widespread hyperalgesia (Figure 3). Similarly, the hyperalgesia in the repeated acid model, or the fatigue-induced model, requires activation of acid sensing ion channel 3 (ASIC3) since the hyperalgesia does not in ASIC3 knockout mice (Sluka et al, 2003, Gregory et al, 2015a)(Figure 3). However, when an ASIC antagonist is given after the development of hyperalgesia, there is no effect on the hyperalgesia, suggesting that once developed the hyperalgesia is independent of nociceptor activation by acidic pH (Karczewski et al, 2010, Gautam et al, 2012).…”
Section: Alterations In Nociceptors May Underlie Some Of the Pathologmentioning
confidence: 99%